Lived Experiences of Interpersonal Trauma and Spiritual Coping among Adolescents: A Transcendental Phenomenological Study - Niken Setyaningrum; Ardhian Indra Darmawan; Eriyono Budi Wijoyo; Tran Thien Nhan (PT.Mantaya Idea Batara, 2026)
Background: Adolescents who experience interpersonal trauma, like bullying, family conflict, emotional neglect, or betrayal in a relationship, are at a higher risk for mental health problems, especially social anxiety and low self-esteem. A lot of research has been done on the effects of trauma, but not much has been done on how teens use spiritual coping as a way to make sense of what happened to them after trauma. Methods: This study utilized a qualitative transcendental phenomenological framework, employing Moustakas’ methodology to investigate adolescents lived experiences of interpersonal trauma and spiritual coping. We did in-depth, semi-structured interviews with 15 teens who had been through trauma in their relationships. The data underwent analysis via epoche, horizontalization, clustering of meaning units, and the formulation of textural and structural descriptions, resulting in a fundamental synthesis of the phenomenon. Results: The analysis showed that there are some things that don't change about experience, such as a broken sense of relational safety, internalized self-blame and silence, emotional withdrawal from social relationships, and increased social anxiety. Spiritual coping became a key experiential resource, providing a private and nonjudgmental space that helped people manage their emotions, think about themselves, and rebuild their confidence. Spiritual practices helped people look at traumatic events in a new way, feel better about themselves, and get their mental health back on track. Discussion: These results show that spiritual coping is more about finding meaning than just being religious. This makes spirituality an important psychological tool for teens who are recovering from trauma. The results add to trauma and coping theories by showing how spirituality can help teens rebuild their sense of self and become more emotionally strong. Conclusion: This study emphasizes the necessity of incorporating spiritual dimensions into trauma-informed psychological and mental health interventions for adolescents, providing phenomenological insights that can guide culturally and contextually appropriate support strategies.